Experiences of Food Insecurity Among Undergraduate Students: “You Can’t Starve Yourself Through School” - Maynard, Merryn Sanders; Meyer, Samantha B; Perlman, Christopher M; Kirkpatrick, Sharon I (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
Canadian post-secondary students are vulnerable to food insecurity, yet lack of examination of this issue has prevented identification of policy and program solutions. This mixed-methods study aimed to characterize the experience of food insecurity among undergraduate students by eliciting barriers to food security, strategies used to manage food and money shortages, and perceived implications for health and academic achievement. Surveys and in-depth interviews were conducted with 14 students who demonstrated compromised financial access to food. Students normalized experiences of food insecurity as typical of post-secondary education but expressed anxiety and frustration with financial inaccessibility to healthy food, and described negative implications for their physical and mental health and their ability to perform well in school. Ongoing attempts to adapt or adjust to food insecurity had limited success. Findings highlight the need to challenge the “starving student” ideology, which normalizes the lack of access to healthy food during higher education.